2020
DOI: 10.3390/jfmk5030053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Continuous Aerobic Training Protocols in a Heterozygous Mouse Model of Niemann-Pick Type C Disease

Abstract: The positive effects of physical activity on cognitive functions are widely known. Aerobic training is known to promote the expression of neurotrophins, thus inducing an increase in the development and survival of neurons, as well as enhancing synaptic plasticity. Based on this evidence, in the present study, we analyze the effects of two different types of aerobic training, progressive continuous (PC) and varying continuous (VC), on synaptic and muscular plasticity in heterozygous mice carrying the genetic mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Since the UC protocol was not found to be effective in Npc1 +/− mice, probably because it was too weak and not demanding enough, we more recently evaluated the influence of exercise on neuroplasticity by subjecting Npc1 +/− mice to more challenging training protocols over a longer period [ 122 ]. Specifically, we administered two aerobic training protocols, progressive continuous (PC) and varying continuous (VC), which differed in terms of speed and velocity changes, as described previously [ 123 ] ( Table 1 ).…”
Section: Additional Non-pharmacologic Approaches For Neurodegenerationmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the UC protocol was not found to be effective in Npc1 +/− mice, probably because it was too weak and not demanding enough, we more recently evaluated the influence of exercise on neuroplasticity by subjecting Npc1 +/− mice to more challenging training protocols over a longer period [ 122 ]. Specifically, we administered two aerobic training protocols, progressive continuous (PC) and varying continuous (VC), which differed in terms of speed and velocity changes, as described previously [ 123 ] ( Table 1 ).…”
Section: Additional Non-pharmacologic Approaches For Neurodegenerationmentioning
confidence: 99%
“…Both protocols had a total duration of 18 min. In addition, training sessions were conducted three times per week for twelve weeks (PCt and VCt, respectively) and, in the case of the VC protocol, also twice per week (VCb) [ 122 ]. Our results showed that the PCt protocol was not efficient enough as demonstrated by impairment in the LTP induction phase, whereas the VCt protocol was even more stressful and completely inhibited synaptic plasticity.…”
Section: Additional Non-pharmacologic Approaches For Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…One mm 3 of muscle tissue from left quadriceps biopsies were fixed in 4% paraformaldehyde and post-fixed in 2% osmium tetroxide (Cariati et al, 2020). After washing with 0.1 M phosphate buffer, the sample was dehydrated by a series of incubations in 30, 50, and 70% ethanol.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%